Cratin. fr. 234 K.-A. - Leonardo Fiorentini (Annali Online dell'Università di Ferrara. Sezione Lettere)
Poll. IV 99 is a test. of Cratin. fr. 234 K.-A., and it confirms the conjecture πόδιζε instead of ms’ tradition σπόδιζε.